Involvement of miRNAs and cell-secreted vesicles in mammalian ovarian antral follicle development - Silveira, Juliano Coelho da; Andrade, Gabriella Mamede; Nogueira, Marcelo Fábio Gouveia [UNESP]; Meirelles, Flávio Vieira; Perecin, Felipe (Springer Nature, 2015)
Ovarian follicular development is a controlled series of events culminating with an ovulatory or atretic follicle. MicroRNAs (miRNAs) are small noncoding RNAs involved in translational regulation of genes in different developmental processes. Deletion of Dicer in mice ovaries demonstrated the importance of miRNAs in reproduction, which led to infertility. The miRNAs were thought to act only within host cells; however, these molecules are also present in cell-secreted vesicles. These vesicles are present in body fluids such as milk, serum, and ovarian follicular fluid. Vesicles are secreted in extracellular fluids and travel from donor to target cells, mediating transfer of bioactive material. Herein we discuss the role of hormonal-regulated miRNAs within different ovarian follicular cells as well as cell-secreted vesicles participation in mammalian ovarian follicular fluid. Furthermore, we discuss the possibility of miRNAs transference mediated by cell-secreted vesicles present in ovarian follicular fluid, increasing the versatility of miRNA functions during antral follicle development.
Keywords: Follicle; Noncoding RNA; Posttranscriptional gene regulation; miRNAs; Cell-secreted vesicles